PRECISION MICROMACHINING OF METALS BY CUBR LASER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The ability to laser machine materials with high resolution and high throughput is critical in advanced manufacturing for a vast array of applications, from photovoltaic cells to bio-compatible micro-components. Copper bromide (CuBr) lasers with their excellent beam quality promised noticeable advantages and improvements in high precision and material processing at the microscale. The application of the CuBr laser as a precision tool for micromachining of different metals has been demonstrated. That good performance was a result of the combination of high power visible radiation, short pulses, and close to the diffraction-limited laser beam divergence with high-speed galvo scanner beam steering.